Plastic zone evolution during fatigue crack growth: Digital image correlation coupled with finite elements method. (15th October 2019) - Hosdez, J.; Langlois, M.; Witz, J-F.; Limodin, N.; Najjar, D.; Charkaluk, E.; Osmond, P.; Forre, A.; Szmytka, F.
Abstract: Nonlinearities effects at the crack tip, due to the elastic-plastic material behavior, impact the crack growth rate and path. This paper is devoted to the study of the plastic zone evolution in the crack tip region. The methodology relies on coupling an elastic-plastic Finite Elements Method (FEM) model and experimental displacements measured by Digital Image Correlation (DIC). These latter are introduced as Dirichlet boundary conditions in the finite elements analysis. The considered FEM domain is constant, i.e. the same mesh with a centered crack is moved to each new crack tip position deduced from DIC. The new boundary conditions are updated and the residual stresses and plastic strains of the former computation are interpolated and actualized on the mesh shifted to the new crack tip position in order to incorporate them in the numerical model. The coupling method allowed applying experimental boundary conditions in order to be as close as possible to real experimental conditions and to observe the plasticity evolution from small to large scale yielding conditions. A fatigue test was conducted to validate the proposed approach. The identification residues are proved to be lower than those obtained with an experimental displacements projection onto Williams' series basis, which is a method commonly used with DIC. The coupling results present an attractive similarity with Irwin's model regardless of the crack length. Thus, the definition of the mask needed for the displacements fields projection on Williams' model can be deduced with a reliable estimate of Irwin's plastic radius.